Reproductive Environmental Health Education During Residency: A Survey of U.S. Obstetrics and Gynecology Residents. (October 2015) - Smith, Patricia A.; Paulson, Jerome; Sutton, Patrice; Stotland, Naomi; Gaba, Nancy
Abstract : APGO Advisor: : Sonya Erickson, MD PURPOSE: To ascertain resident opinion about their formal training in reproductive environmental health. BACKGROUND: Obstetrician–gynecologists are well positioned to help patients recognize and avoid hazardous environmental exposures. The status of formal residency education on endocrine disrupting chemicals (EDCs) in the environment is currently unknown. The perspective of the residents about that education is similarly unknown. METHODS: A validated survey was modified and distributed electronically to the 216 U.S. obstetrics and gynecology residency programs, with the request to distribute it to their residents. Respondents reported their level of knowledge and confidence discussing routine topics (eg, weight gain, smoking) as well as environmental exposures (eg, BPAs, pesticides). They also indicated whether they felt adequately trained on environmental health. EVALUATION PLAN: One hundred sixteen residents responded. Seventy percent reported high knowledge regarding smoking or weight gain. Conversely, more than 80% reported minimal or no knowledge of EDCs on reproductive health. Eighty-one percent felt their institution probably or definitely does not provide adequate training on reproductive environmental health topics. DISSEMINATION: Findings will be presented at 2015 Association of Professors of Obstetrics and Gynecology/Council on Resident Education in Obstetrics and Gynecology meeting. REFLECTIVE CRITIQUE: Obstetrics and gynecology residents reported a need for improved training in reproductive environmental health. Modules on environmental health will be developed, with learning assessed using premodule and postmodule assessment tools.